Heavy metals in reindeer and their forage plants - Eriksson, O.; Frank, A.; Nordkvist, M.; Petersson, L. R. (Rangifer, 1990)
An attempt was made to assess the level of heavy metal transfer from forage plants to reindeer (Rangifer tarandus L.) in an area in northern Lapland affected from dust from an open pit copper mine. Botanical analyses of rumen contents from reindeer provided information about the main plant species in the diet. Representative plant material was collected from sample plots within an 8 km radius from the central part of the mine and from a reference area situated about 200 km upwind of the mining site. The following plant species were analysed: Bryoria jremontii, Br. juscescens, Cladina rangiferina, Equisetum fluviatile, Descbampsiaflexuosa, Eriopborum vaginatum, Salix glauca, Salix pbylicifolia, Betula nana, and Vaccini-um myrtillus. The greatest difference between metal concentrations in the plants collected from dust contaminated area and from the reference area was found in lichens. Copper is the main metallic component of the ore and was found in higher concentrations in lichens coming from the area around the mine than in lichens from the reference area. Smaller differences were found in vascular plants. Dust particles, remaining on outer surfaces after snow smelt contributed to a limited extent to the metal contents. Species—specific accumulation of metals was observed in some plants. The uptake of lead and cadmium in some vascular plants was somewhat higher in the reference area compared with plants growing in the perifery of the mining center, probably due to the metal concentrations in the bedrock. Organ material (liver and kidney) was collected from reindeer in both areas. No noticable effect on metal concentrations in the liver of the reindeer were found. Although the lead, cadmium and copper concentrations were higher in the organs collected from animals in the reference area than in those from the mining area, the levels were still below the concentrations regarded as harmful for the animals from toxicological point of view. The material collected during this study would also lend itself to research into the trace element nutrition of the reindeer.